Handbook of child sexual abuse : identification, assessment, and treatment - Goodyear-Brown, Paris (John Wiley & Sons, 2012)
This book is a comprehensive guide to the identification, assessment, and treatment of child sexual abuse. The field of child sexual abuse has experienced an explosion of research, literature, and enhanced treatment methods over the last thirty years. Representing the latest refinements of thought in this field, this volume combines the most current research with a wealth of clinical experience. The contributing authors, many of whom are pioneers in their respective specialties, include researchers and clinicians, forensic interviewers and law enforcement professionals, caseworkers and victim advocates, all of whom do the work of helping children who have been sexually victimized. Offering a snapshot of the state of the field as it stands today, the authors explore a variety of issues related to child sexual abuse, from identification, assessment, and treatment methods to models for implementation and prevention, including: The impact of sexual abuse on the developing brain; The potential implications of early sexual victimization; Navigating the complexities of multidisciplinary teams; Forensic interviewing and clinical assessment; Treatment options for children who have traumagenic symptoms as a response to their sexual victimization; Treating children with sexual behavior problems and adolescents who engage in illegal sexual behavior; Secondary trauma and vicarious traumatization; and Cultural considerations and prevention efforts. Edited by a leader in the field of child therapy, this important reference equips helping professionals on the front lines in the battle against child sexual abuse- not merely with state-of-the-art knowledge, but also with a renewed vision for the importance of their role in the shaping of our culture and the healing of victimized children